Extrahepatic recurrence rates in patients receiving adjuvant hepatic artery infusion and systemic chemotherapy after complete resection of colorectal liver metastases. Issue 8 (25th September 2020) - Srouji, Rami M.; Narayan, Raja R.; Boerner, Thomas; Buisman, Florian E.; Seier, Kenneth; Gonen, Mithat; Balachandran, Vinod P.; Drebin, Jeffrey A.; Jarnagin, William R.; Kingham, T. Peter; Wei, Alice; Kemeny, Nancy E.; et al.
Abstract: Background: This study investigated the effect of the reduced dose of systemic chemotherapy (SYS) on recurrence patterns in patients receiving adjuvant hepatic artery infusion (HAI) chemotherapy after complete colorectal liver metastases (CRLM) resection. Methods: Patients undergoing complete CRLM resection between 2000 and 2007 were selected from a prospectively maintained database and categorized as receiving SYS or HAI + SYS. Those with pre and/or intraoperative extrahepatic disease, documented death, or recurrence within 30 days of CRLM resection were excluded. Competing risk, Fine and Gray's tests were used to compare SYS versus HAI + SYS for time‐to‐organ recurrence. Results: Of 361 study patients, 153 (42.4%) received SYS and 208 (57.6%) received HAI + SYS. The median follow‐up for survivors was 100 (range = 12–185) and 156 months (range = 18–217) for SYS and HAI + SYS, respectively. The 5‐year cumulative incidence (CI) of any liver recurrence was greater for those receiving SYS (SYS = 41.9% vs. HAI + SYS = 28.6%, p = .005). The 5‐year CI of developing any lung or extrahepatic recurrence for SYS patients was 36.2% and 47.9% compared with 44.5% ( p = .242) and 51.7% ( p = .551), respectively, in patients receiving HAI + SYS. Conclusion: Despite the reduced dose of SYS, adjuvant HAI + SYS after CRLM resection is not associated with a significantly increased risk of extrahepatic recurrence.